IMPLIKASI UNDANG-UNDANG NOMOR 4 TAHUN 2023 TENTANG PENGEMBANGAN DAN PENGUATAN SEKTOR KEUANGAN TERHADAP TUGAS DAN FUNGSI PPATK - TRI INDAH PURWANTI; ANNA MARIA; NINING WIDYANINGRUM; THEODORUS SENDJAJA (FEB Universitas Sam Ratulangi Manado, 2024)
The implementation of Law Number 4 of 2023 on Financial Sector Development and Strengthening (PPSK Law) is a strategic step in strengthening Indonesia's financial system amid complex global challenges. This law emphasizes the importance of supervision of financial activities, particularly in the prevention of money laundering (TPPU) and terrorism financing (TPPT). The Financial Transaction Reports and Analysis Center (PPATK) has a central role in the implementation of this law, with duties expanded to include data integration and inter-agency cooperation. This study analyzes the implications of the PPSK Law on PPATK's duties and functions, as well as the challenges faced in the implementation of financial crime supervision and prevention. The results show that strengthening PPATK's capacity, both in terms of human resources and technology, is crucial to achieving the objectives of this law and maintaining the stability of the national financial sector.